Violence without Truce: Hondurans in the Gulf of Mexico Corridor. (November 2022) - Rodríguez L., María Teresa
The Mexican states of Chiapas and Tabasco have for decades been linked to Central American migrations, largely through cross-border labor mobility. Today, however, the diversification of receiving areas in Mexico requires focusing attention on how the dynamics of mobility, settlement, and/or transit impact new contexts. The state of Veracruz, part of the so-called Gulf of Mexico corridor that connects the country's southern and northern borders on the east, has emerged as an unplanned destination—a place of temporary or permanent residence—for Central American migrants, especially Hondurans. Examination of the types of violence experienced by in-transit undocumented migrants and temporary or permanent residents in the area shows how the coercive migration policies of the Mexican government contribute to maintaining a continuum of violence that affects people "trapped in mobility." Los estados mexicanos de Chiapas y Tabasco han estado vinculados durante décadas a las migraciones centroamericanas, en gran parte a través de la movilidad laboral transfronteriza. Hoy, sin embargo, la diversificación de las áreas receptoras en México requiere que enfoquemos la atención en cómo la dinámica de movilidad, asentamiento y/o tránsito impacta en nuevos contextos. El estado de Veracruz, parte del llamado corredor del Golfo de México que conecta las fronteras sur y norte del país en el lado este, se ha convertido en un destino no planificado, un lugar de residencia temporal o permanente, para los migrantes centroamericanos, especialmente los hondureños. Un análisis de los tipos de violencia que experimentan los migrantes indocumentados en tránsito y los residentes temporales o permanentes en la zona muestra cómo las políticas migratorias coercitivas del gobierno mexicano contribuyen a mantener un ciclo de violencia que afecta a aquellos "atrapados en la movilidad".